BRIEF DESCRIPTION OF CASES CONSIDERED UNDER THE SIMPLIFIED PROCEDURE - Pirmatov Otabek Shavkatovich (Miasto Przyszłości, 2025)
This article describes the specific features of the consideration of economic cases in the simplified procedure. The article describes the specific features of the simplified procedure: holding a court hearing without the participation of the parties, only written proceedings, prohibition of the use of certain means of evidence, active participation of the court in the proceedings, the procedure for conducting a case without a court hearing, and other procedural procedures.